Surfactant Protein A Polymorphism Is Associated with Susceptibility to Chronic Obstructive Pulmonary Disease (COPD) in Chinese Uighur Population - 关键 刘先胜 谢俊刚 许西琳 骆树新 王苒 徐永健 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
This study investigatedexamined the correlation between surfactant protein-A (SP-A) polymorphism and the susceptibility of cvhronic obstructive pulmonary disease (COPD) in Xinjiang Uighurs. Genomic DNA was extracted from peripheral blood of 194 COPD smokers and 201 healthy smokers of Uighur who were hospitalized in or paid a visit to one of the four Xingjiang-based hospi-tals involved in the study, betweenfrom March 2009 to December 2010. Single nucleotide polymor-phisms (SNPs) were studied on A/G atwithin amino acid aa62 (CCA/CCG rs1136451) and C/T within aa219 (CGG/TGG, rs4253527) in SP-A. Genotypes were determined by using the TaqMan polymerase chain reaction (PCR). Our results showed that genotype frequencies were different be-tween the COPD and normal smokers infor aa62 (χx2=6.852, P=0.033). There were also significant differences in allele genotype frequencies between the COPD and the control and allele G might de-crease the risk COPD (χx2=6.545, P=0.011; OR=0.663; 95% CI: 0.484-0.909). The result suggested We were led to conclude that polymorphism of aa62 (CCA/CCG, rs1136451) of SP-A may be asso-ciated with the susceptibility to COPD in Xingjiang Uighurs.